Indian Agriculture: Role of Extension in the Changing Agriculture Scenario - Ratnakar, R. (International Journal of Economic Plants, 2016)
The extension services in India are highly pluralized. Numerous agencies are now providing extension service in varied nature through different approaches.As agriculture is a state subject, each state has its own programmes and policies to support extension services to its farming community. Various Central Government Ministries (Agriculture, Commerce, IT, Rural Development etc.) have their own programmes and schemes to support the states in strengthening their farmer oriented services.The challenges to agriculture and natural resource management are unprecedented in the history of mankind and this has led to changes in agriculture education, research and extension world over. The development of sustainable Agriculture in a country will depend largely on the effectiveness of its Agriculture Extension strategies, its approaches, services delivery, methodology and processes. Farmer empowerment is the desired outcome of agriculture development and it can be achieved through engagement, learning and participation in the research and extension processes.Agriculture Extension has been the cornerstone of the agricultural development in the country rising from a food deficit to a food export economy in about 30 years.The critical role that extension plays is to expand the horizon of farmers, in terms of their knowledge, skills and attitudes about the management of natural, economic & social resources at their disposal.